The International Spillovers of Capital Income Taxation An Applied General Equilibrium Analysis - Delorme, François (OECD Publishing, 1993)
This paper sheds light on the complex macroeconomic effects initiated by capital income taxation using a dynamic applied general equilibrium model of the U.S. economy. The model considers impacts of policy changes on the allocation of resources across both industries and countries, and over time. Within the model, a given change in capital income taxation abroad affects the domestic economy through capital flows, commodity flows and tax revenue effects. Thus, the model considers the spillovers associated with changes in commodity flows in addition to the usual spillovers generated by capital movements. The simulation results illustrate rather well that personal and corporate income taxation yield very different conclusions in terms of macroeconomic consequences and that it is important to distinguish between short- and long-run policy implications of the two types of capital income tax policies ...
Keywords: Economics